2015
DOI: 10.5935/1806-0013.20150064
|View full text |Cite
|
Sign up to set email alerts
|

Primary auriculotemporal neuralgia. Case report

Abstract: BACKGROUND AND OBJECTIVES:Auriculotemporal neuralgia is an uncommon condition. Symptoms are brief severe pain attacks, especially in the temporal region. Although many cranial neuralgias are related to nervous compression, they may be present without identifiable etiologic factors. This study aimed at describing a case of primary auriculotemporal neuralgia and respective therapeutic approach. CASE REPORT: Male patient, 72 years old, presented for assistance reporting severe pain in left temporal region, descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Nevertheless, the duration of the effect was short (24 h-10 days). ATN is a rare disorder and treatments proposed in the literature are not evidence-based; therefore, most clinicians prescribe medications used in other forms of neuralgia, such as gabapentin or carbamazepine [9][10][11][12]; in our cohort, the patients that were on medications had no significant pain relief with these drugs. Treatment with BoNT/A injections had been previously reported in only one case of ATN with satisfactory results [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the duration of the effect was short (24 h-10 days). ATN is a rare disorder and treatments proposed in the literature are not evidence-based; therefore, most clinicians prescribe medications used in other forms of neuralgia, such as gabapentin or carbamazepine [9][10][11][12]; in our cohort, the patients that were on medications had no significant pain relief with these drugs. Treatment with BoNT/A injections had been previously reported in only one case of ATN with satisfactory results [18].…”
Section: Discussionmentioning
confidence: 99%
“…Speciali et al described six patients with ATN in 2005 [9]; all the patients were female and all of them had unilateral pain which worsened with palpation over the preauricular region, with secondary pain radiation toward the mandible in all cases, and toward the occipital region in four cases. The presence of concomitant background pain is not uncommon [10][11][12]. Ruiz et al reported eight patients with ATN: two patients had only background pain, two patients had both background pain and paroxysmal stabbing pain, while the last four patients only had paroxysmal pain (two of them had stabbing pain, one had shock-like pain and one had throbbing pain); exacerbation pain lasted from 2 s to 30 min and was mainly localized in the temporal, preauricular, and periauricular regions, but there was also hemicraneal and lateral neck localization and/or pain radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auriculotemporal neuralgia (ATN) is a rare disorder involving 0.23–0.4% of the patients in tertiary headache centers, characterized by unilateral side-locked pain localized in the territory of the auriculotemporal nerve [ 1 , 2 , 3 , 4 ]. The pain could be paroxysmal, moderate to severe in intensity, and variable in duration; however, continuous pain is often seen in this scenario.…”
Section: Introductionmentioning
confidence: 99%